Impact of sand mining on sediment transport and morphological change of Hai Phong coastal area - Hai, Nguyen Minh; Khanh, Do Gia; Vinh, Vu Duy; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2019)
The paper presents the results of simulating the impact of sand mining on sediment transport and morphological change in Hai Phong coastal area based on Delft3D model. Scenario groups are established: Present scenarios without sand mining and simulated scenarios of the present sand mining (assuming 30% sand compared to plan). The scenario groups are calculated in the dry and rainy seasons for main wind directions (NE, SE, SW) in the case of moderate wind and strong wind. The results show that sand mining reduces sediment flow alongshore (2–81%) and seawards (5–83%). Besides, the increase in depth causes morphological change in this area: Rising the deposition rate (5–10 mm/month) at the sand mining locations; decreasing accretion rate and increasing the erosion rate in the neighboring areas of sand mining location